A Test Case Generation Method for Workflow Systems Based on I/O_WF_Net - Shanling Li; Changyou Zheng; Yaqing Shi; Sainan Zhang (Tehnički Vjesnik, 2023)
At present, the testing of the workflow system is mainly based on manual testing, and the functions of only some tools are relatively simple. The design of test cases mainly depends on the experience of testers, which makes the lack of test coverage. In this paper, a test case generation method based on the I/O_WF_Net model is proposed. A test case generation algorithm that satisfies the process branch coverage criterion is designed, which solves the problem of automatic test case generation for workflow systems. The algorithm divides the model according to "split-merge pairs" to generate a decomposition tree of the model, and then traverses the tree to generate test cases. A workflow system modelling and test case generation tool are designed and implemented, and an actual workflow system is used as the experimental object to verify the effectiveness of the method.